2013
DOI: 10.1161/circresaha.111.300581
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein AI and High-Density Lipoprotein Have Anti-Inflammatory Effects on Adipocytes via Cholesterol Transporters

Abstract: Rationale Macrophage accumulation in adipose tissue associates with insulin resistance and increased cardiovascular disease risk. We previously have shown that generation of reactive oxygen species (ROS) and monocyte chemotactic factors after exposure of adipocytes to saturated fatty acids (SFAs) such as palmitate occurs via translocation of NADPH oxidase 4 (NOX4) into lipid rafts (LRs). The anti-inflammatory effects of apolipoprotein A-I (apoA-I) and HDL on macrophages and endothelial cells appears to occur v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
115
4

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 105 publications
(127 citation statements)
references
References 55 publications
8
115
4
Order By: Relevance
“…Lipid rafts in differentiated adipocytes was detected following incubation with 1 mg/mL Alexa Fluor 594-conjugated cholera toxin subunit-b (Molecular Probes) for 15 min at 4°C, as previously described (4,6). Indeed, binding of cholera toxin subunit-b to the pentasaccharide chain of plasma membrane ganglioside G M1 , which selectively partitions into lipid rafts (18), allows the reliable detection of lipid rafts in live cells.…”
Section: Quantification Of Lipid Raftsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lipid rafts in differentiated adipocytes was detected following incubation with 1 mg/mL Alexa Fluor 594-conjugated cholera toxin subunit-b (Molecular Probes) for 15 min at 4°C, as previously described (4,6). Indeed, binding of cholera toxin subunit-b to the pentasaccharide chain of plasma membrane ganglioside G M1 , which selectively partitions into lipid rafts (18), allows the reliable detection of lipid rafts in live cells.…”
Section: Quantification Of Lipid Raftsmentioning
confidence: 99%
“…ABCG1 is expressed in adipocytes and in adipose tissue of mice that develop diet-induced obesity (5,6). Moreover, adipose tissue is a major source of LPL (7), which critically controls TG accumulation by generating free fatty acids from circulating lipoproteins (8).…”
mentioning
confidence: 99%
“…In this regard, activation of the PI3K/AKT pathway by SR-B1 ligands provides an essential survival signal for tumor cells [84,85]. A third mechanism of SR-B1 to promote tumor growth is by the inhibition of acute inflammation [73,74]. SR-B1 has been implicated in several biological processes such as apoptosis [86,87] entry through TRPC3 channels, leading to dampened cytokine production in response to CpG via TLR9 activation [90].…”
mentioning
confidence: 99%
“…ApoA-I and HDL have been shown to have antiinflammatory properties in adipocytes similarly to what has been observed in macrophages and endothelial cells. It was found that both HDL and ApoA-I inhibit palmitate-mediated gene induction of pro-inflammatory chemotactic factor (e.g., monocyte chemotactic protein-1, serum amyloid A3) in cultured adipocytes (Umemoto et al 2013). Furthermore, there was a reduction in chemotactic factor expression and macrophage accumulation in ApoA-I transgenic mice fed a high-fat diet compared to similarly treated control mice (Umemoto et al 2013).…”
Section: Effects Of Hdl On Obesitymentioning
confidence: 99%
“…It was found that both HDL and ApoA-I inhibit palmitate-mediated gene induction of pro-inflammatory chemotactic factor (e.g., monocyte chemotactic protein-1, serum amyloid A3) in cultured adipocytes (Umemoto et al 2013). Furthermore, there was a reduction in chemotactic factor expression and macrophage accumulation in ApoA-I transgenic mice fed a high-fat diet compared to similarly treated control mice (Umemoto et al 2013). Because macrophage accumulation and adipose tissue inflammation are strongly correlated with insulin resistance, these observations provide potential implications for the prevention and management of insulin resistance.…”
Section: Effects Of Hdl On Obesitymentioning
confidence: 99%